Impact of the emergence of non‐vaccine pneumococcal serotypes on the clinical presentation and outcome of adults with invasive pneumococcal pneumonia. (14th May 2012) - Burgos, J.; Falcó, V.; Borrego, A.; Sordé, R.; Larrosa, M. N.; Martinez, X.; Planes, A. M.; Sánchez, A.; Palomar, M.; Rello, J.; Pahissa, A.
Abstract The introduction of the 7‐valent pneumococcal conjugate vaccine in children has led to a change in the pattern of pneumococcal serotypes causing pneumococcal disease. The aim of this study was to compare the clinical presentation and outcome of invasive pneumococcal pneumonia (IPP) in adults between the pre and post‐vaccine era. We have conducted an observational study of all adults hospitalized with IPP, from 1996 to 2001 (pre‐vaccine period), and from 2005 to 2009 (post‐vaccine period). Incidence, serotype distribution and clinical data were compared between both periods. A total of 653 episodes of IPP were diagnosed. The overall incidence of IPP increased from 14.2 to 17.9 cases per 100 000 population‐year (p 0.003). In the post‐vaccine period IPP caused by vaccine serotypes decreased (−36%; 95% CI, −52 to −15) while IPP caused by non‐vaccine serotypes increased (71%; 95% CI, 41–106). IPP in the post‐vaccine period was associated with higher rates of septic shock (19.1% vs. 31.1%, p <0.001). Among patients aged 50–65 years there was a trend towards a greater proportion of case‐fatalities (11.6–23.5%, p 0.087). Independent risk factors for septic shock were IPP caused by serotype 3 (OR 2.38; 95% CI, 1.16–4.87) and serotype 19A (OR 6.47, 95% CI, 1.55–27). Serotype 1 was associated with a lower risk of death (OR 0.1; 95% CI, 0.01–0.78). In conclusion, the incidence of IPP in the post‐vaccine period has increased in our setting, it is caused mainly by non‐vaccine serotypes and it is associated with higher rates of septic shock.